Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\sqrt{17}-4\) b) \(\sqrt{3}\) c) \(\frac{\sqrt{2}}{2}\) d)\(\frac{\sqrt{x}+1}{\sqrt{x}-1}\) e) \(x-\sqrt{5}\)
f) \(4+2\sqrt{3}\) g) \(3+2\sqrt{2}\) h) \(x+\sqrt{x}+1\) i) \(\frac{3\sqrt{5}-\sqrt{15}}{10}\)
k) \(\sqrt{5}+\sqrt{6}\) i) 5 h) 0 l) \(\sqrt{5}+\sqrt{3}\) m) \(\frac{20\sqrt{3}}{3}\) d) 0
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\frac{3-\sqrt{3}}{\sqrt{3}}=\frac{\sqrt{3}\left(\sqrt{3}-1\right)}{\sqrt{3}}=\sqrt{3}-1\)
b)\(\frac{2\sqrt{2}+\sqrt{6}}{4+\sqrt{12}}=\frac{\sqrt{2}\left(2+\sqrt{3}\right)}{2\left(2+\sqrt{3}\right)}=\frac{\sqrt{2}}{2}\)
c)\(\frac{1-\sqrt{a^3}}{a-1}=\frac{1-\sqrt{a}^3}{-\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)}=\frac{-\left(1-\sqrt{a}\right)\left(1+\sqrt{a}+a\right)}{\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)}=\frac{-1-\sqrt{a}-a}{1+\sqrt{a}}\)
d)\(\frac{\sqrt{6+2\sqrt{5}}}{\sqrt{5}+1}=\frac{\sqrt{5+2\sqrt{5}+1}}{\sqrt{5}+1}=\frac{\sqrt{\left(\sqrt{5}+1\right)^2}}{\sqrt{5}+1}=\frac{\left|\sqrt{5}+1\right|}{\sqrt{5}+1}=\frac{\sqrt{5}+1}{\sqrt{5}+1}=1\)
e)\(\frac{\sqrt{5+2\sqrt{6}}}{\sqrt{3}+\sqrt{2}}=\frac{\sqrt{3+2\sqrt{6}+2}}{\sqrt{3}+\sqrt{2}}=\frac{\sqrt{\left(\sqrt{3}+\sqrt{2}\right)^2}}{\sqrt{3}+\sqrt{2}}=\frac{\left|\sqrt{3}+\sqrt{2}\right|}{\sqrt{3}+\sqrt{2}}=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2.1
\(A=\sqrt{6+2\sqrt{5}}-\sqrt{6-2\sqrt{5}}=\sqrt{5+2\sqrt{5.1}+1}-\sqrt{5-2\sqrt{5.1}+1}\)
\(=\sqrt{(\sqrt{5}+1)^2}-\sqrt{(\sqrt{5}-1)^2}=|\sqrt{5}+1|-|\sqrt{5}-1|=2\)
2.2
\(B\sqrt{2}=\sqrt{8+2\sqrt{15}}+\sqrt{8-2\sqrt{15}}-2\sqrt{6-2\sqrt{5}}\)
\(=\sqrt{3+2\sqrt{3.5}+5}+\sqrt{3-2\sqrt{3.5}+5}-2\sqrt{5-2\sqrt{5.1}+1}\)
\(=\sqrt{(\sqrt{3}+\sqrt{5})^2}+\sqrt{(\sqrt{3}-\sqrt{5})^2}-2\sqrt{(\sqrt{5}-1)^2}\)
\(=|\sqrt{3}+\sqrt{5}|+|\sqrt{3}-\sqrt{5}|-2|\sqrt{5}-1|=2\)
$\Rightarrow B=\sqrt{2}$
Bài 1:
1. ĐKXĐ: \(\left\{\begin{matrix} 2x-1\geq 0\\ x-3\geq 0\\ 5-x>0\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} x\geq \frac{1}{2}\\ x\geq 3\\ x< 5\end{matrix}\right.\Leftrightarrow 3\leq x< 5\)
2.
ĐKXĐ: \(\left\{\begin{matrix} x-1\geq 0\\ 2-x\geq 0\\ x+1>0\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} x\geq 1\\ x\leq 2\\ x>-1\end{matrix}\right.\Leftrightarrow 1\leq x\leq 2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài rút gọn
\(\sqrt{\left(x-1\right)^2}-x=\left|x-1\right|-x\)
\(=\left(x-1\right)-x=x-1-x=-1\left(x>1\right)\)
Bài gpt:
\(\sqrt{x^2-3x+2}+\sqrt{x^2-4x+3}=0\)
Đk:\(-1\le x\le3\)
\(pt\Leftrightarrow\sqrt{\left(x-1\right)\left(x-2\right)}+\sqrt{\left(x-1\right)\left(x-3\right)}=0\)
\(\Leftrightarrow\sqrt{x-1}\left(\sqrt{x-2}+\sqrt{x-3}\right)=0\)
Dễ thấy:\(\sqrt{x-2}+\sqrt{x-3}=0\) vô nghiệm
Nên \(\sqrt{x-1}=0\Rightarrow x-1=0\Rightarrow x=1\)
\(x=6-2\sqrt{5}\)
\(x=\sqrt{5}^2-2\sqrt{5}+1\)
\(x= \left(\sqrt{5}-1\right)^2\)
thay vào P ta đc:
\(P=\frac{2\sqrt{\left(\sqrt{5}-1\right)^2}-1}{\sqrt{\left(\sqrt{5}-1\right)^2}+1}\)
\(P=\frac{2\left(\sqrt{5}-1\right)-1}{\sqrt{5}-1+1}\)
\(P=\frac{2\sqrt{5}-2-1}{\sqrt{5}}\)
\(P=\frac{2\sqrt{5}-3}{\sqrt{5}}\)
\(P=\frac{10-3\sqrt{5}}{5}\)